Workload, Life Satisfaction and Intention to Leave in Hotel Businesses - İbrahim Yikilmaz; Lütfi Sürücü; İlkay Güleryüz (Journal of Tourism and Gastronomy Studies, 2023)
The aim of this study is to investigate the impact of life satisfaction and workload levels on the intention to leave among personnel working in accommodation establishments. The sample includes 225 employees working in Istanbul hotels that have a tourism management certificate. The study's results suggest that workload has a positive effect on turnover intention, while life satisfaction has a negative effect. Additionally, life satisfaction can mediate the interaction between workload and intention to leave. The study's results suggest that increasing employee life satisfaction levels can help reduce negative workplace experiences caused by workload and intention to leave. These negative experiences are a significant problem that can reduce productivity and customer satisfaction in accommodation businesses. The study expands on the literature on workload and intention to leave by empirically examining the role of life satisfaction in the field. Furthermore, the study offers important suggestions for effective and sustainable management practices in hotel and accommodation businesses.
Keywords: 330; Life satisfaction; İntention to leave; Workload; Job demands; Hospitality industry